Polycystic Ovary Syndrome: A literature review (Research, Society and Development, 2026)
Objective: To conduct a systematic analysis of Polycystic Ovary Syndrome (PCOS), including its characteristics and symptoms. Literature review: As an endocrine disorder, polycystic ovary syndrome is common in women of reproductive age. The main symptoms of PCOS are menstrual irregularity, excess hair growth (hirsutism), hair loss (androgenetic alopecia), polycystic ovaries in the ovaries, and difficulty getting pregnant (infertility). The main complications include weight gain (obesity), insulin resistance, which can increase the risk of developing type 2 diabetes, and psychological problems such as mood swings, anxiety, and depression. Acne and dark spots (acanthosis nigricans) can also trigger psychological factors in women with this syndrome, such as low self-esteem.Physical exercise combined with good eating habits is one of the treatments. Final considerations: PCOS is a metabolic endocrine disorder that affects women during their reproductive years and causes various physical and psychological problems. Therefore, it is extremely important to have a thorough medical evaluation based on some of the symptoms mentioned, so that early diagnosis can be made and treatment can be successful. Pharmacological treatment for women with this syndrome should also be prioritized, such as physical activity and a balanced diet.